Pengembangan Pariwisata Berbasis Komunitas di Desa Aneuk Laot Aceh - Somad, Djohari; Rahmanita, Myrza (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study explores community-based tourism (CBT) development in Aneuk Laot Village, Sabang City, as a strategy to support Sustainable Development Goals (SDGs). Methodology/approach: A qualitative case study was conducted using interviews, observations, and a literature review. The informants included Pokdarwis, traditional leaders, and BUMDes managers. Results/findings: The tourism potential of Aneuk Laot includes natural (Lake Aneuk Laot, forests, hills), cultural (traditional customs), and culinary tourism. Effective CBT is driven by active community participation, including youth, women, and local institutions such as Pokdarwis, BUMDes, and traditional leaders. This collaborative model supports the preservation of local assets and contributes to the achievement of the SDGs. Conclusions: The development of community-based tourism (CBT) in Gampong Aneuk Laot contributes significantly to the achievement of the SDGs through cultural preservation, environment, and community empowerment. The active involvement of youth, women, and indigenous groups in tourism management creates jobs, increases income, and strengthens the ownership of local resources. This model promotes sustainable development from social, economic, and ecological aspects. Limitations: This research is limited to examining how community-based tourism development can support sustainable development goals (SDGs) in a region.  There are many other areas which can be studied both in the tourism sector and in other sectors as supporting sustainable development goals (SDGs) Contribution: The research results can be useful for community-based tourism studies and various types of studies supporting sustainable development goals (SDGs).